1994
DOI: 10.1111/j.1467-9817.1994.tb00057.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between musical ability and literacy skills

Abstract: Research has shown that a relationship exists between phonological awareness and literary skills. It has been suggested that a structured programme of musical activities can be used to help children develop a multi-sensory awareness and response to sounds. The relationship between musical ability and literacy skills was examined in a study that showed an association between rhythmic ability and reading. A further pilot intervention study showed that training in musical skills is a valuable additional strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
2
6

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(125 citation statements)
references
References 7 publications
7
110
2
6
Order By: Relevance
“…Thus, the present results provide an explanation why musical elements participate very early in the process of language development in children: it has been hypothesized that music and speech are intimately connected in early life (Trainor and Trehub, 1992;Trehub et al, 2000), that musical elements pave the way to linguistic capacities earlier than phonetic elements (Papoušek, 1996), and that melodic aspects of adult speech to infants represent the infant's earliest associations between sound patterns and meaning (Fernald, 1989), as well as between sound patterns and syntactic structure (Krumhansl and Jusczyk, 1990;Jusczyk et al, 1992;Jusczyk and Krumhansl, 1993). Improvement of abilities in the language domain by training in the musical domain has also been reported for adults (Chan et al, 1998;Douglas and Willatts, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present results provide an explanation why musical elements participate very early in the process of language development in children: it has been hypothesized that music and speech are intimately connected in early life (Trainor and Trehub, 1992;Trehub et al, 2000), that musical elements pave the way to linguistic capacities earlier than phonetic elements (Papoušek, 1996), and that melodic aspects of adult speech to infants represent the infant's earliest associations between sound patterns and meaning (Fernald, 1989), as well as between sound patterns and syntactic structure (Krumhansl and Jusczyk, 1990;Jusczyk et al, 1992;Jusczyk and Krumhansl, 1993). Improvement of abilities in the language domain by training in the musical domain has also been reported for adults (Chan et al, 1998;Douglas and Willatts, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that rhythmic deficits are tied to language impairment: abnormally poor reading and phonological awareness have been linked to difficulties with rhythm skills as diverse as synchronization (Thomson, Fryer, Maltby, & Goswami, 2006; Thomson & Goswami, 2008;Corriveau & Goswami, 2009;Tierney & Kraus, 2013b;Flaugnacco et al, 2014), beat extraction (David, Wade-Wolley, Kirby, & Smithrim, 2007), metrical perception (Huss, Verney, Fosker, Mead, & Goswami, 2011), rhythm memory (Dellatolas, Watier, Le Normand, Lubart, & Chevrie-Muller 2009;González-Trujillo, Defior, & Gutiérrez-Palma, 2012;Flaugnacco et al 2014), and rhythm discrimination (McGivern, Berka, Languis, & Chapman, 1991;Douglas & Willatts, 1994;Strait, Hornickel, & Kraus, 2011). In fact, links between synchronization ability and reading readiness skills have even been observed in pre-schoolers too young to have received reading instruction (Woodruff Carr, White-Schwoch, Tierney, Strait, & Kraus, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Results demonstrated that these children were able to keep up with their peers in all areas of the school curriculum, while performing slightly better than their peers in language and reading skills (Spychiger et al, 1993). These may not seem dramatic results (and the possibility that increased motivation was a key factor cannot be ruled out), however, when considered in the light of studies demonstrating similar improvements in language and reading skills (Hurwitz et al, 1975, Douglas andWillatts, 1994) the theory is strengthened.…”
mentioning
confidence: 99%